Early discharge following transcatheter aortic valve implantation: a feasible goal during the learning curve? - Raquel Pimienta González; Alejandro Quijada Fumero; Marcos Farráis Villalba; Javier Lorenzo González; Ana Laynez Carnicero; Alejandro Iriarte Plasencia; Gabriela Noemí González Chiale; Cristina López Ferraz; Juan Manuel Llanos Gómez; Martín Caicoya Boto; Ángel López Castillo; Julio Salvador Hernández Afonso (REC: Interventional Cardiology (English Ed.))
ABSTRACT Introduction and objectives: Although early discharge protocols after transcatheter aortic valve implantation (TAVI) have demonstrated to be safe in various studies, they are usually applied in high-experience centers. This study analyzes the length of stay of the first 100 patients undergoing TAVI in a center without on-site cardiac surgery, differentiating between very early (< 24 hours), early (24-48 hours), and late discharge (> 48 hours). Furthermore, the study evaluates the feasibility of an early discharge protocol during the team’s learning curve. Methods: We conducted a prospective observational study from April 2022 through January 2024. A preand postoperative management protocol was implemented, including assessments in the Valvular Heart Disease Clinic, admission to the cardiac surgery intensive care unit with electrocardiographic monitoring, and specific discharge criteria in full compliance with an established protocol for the management of conduction disorders. Early follow-up evaluations were performed in the outpatiently after discharge. Results: A total of 100 patients (50% women) were included, with a mean age of 82.4 ± 5.3 years and a EuroSCORE II score of 4.38 ± 5.1%. The median length of stay was 2 days (range, 1-19). A total of 27.27% of patients were discharged in < 24 hours, 48.49% within the 24-48 hours following implantation, and 24.24% 48 hours later. The 30-day cardiovascular mortality rate was 1%. A total of 6 patients were readmitted with procedural complications within the first 30 days. Conclusions: The implementation of a standardized care protocol allows for early and safe discharge in most patients, even during the team’s learning cuve.